Tricked - Calonita, Jen (Calonita, Jen. Fairy Tale Reform School., 2017)
Gilly is bored at Jack of All Trades School where she learns all about shoe leather and measuring feet. Then her sister Anna gets sent to Fairy Tale Reform School where the trickster Rumpelstiltskin has taken over management. Gilly is concerned for Anna and decides the only way to get Anna out is for Gilly to get thrown back into the school.